RESPON VENEZUELA TERHADAP KEHADIRAN MILITER AMERIKA SERIKAT DI KOLOMBIA - Pratiwi, Diah Ayu (Universitas Riau Kepulauan, 2012)
The focus of this paper is about defense cooperation agreement (DCA) between Colombia and the United States on August 14, 2009. The agreement raises concerns for the countries of the anti-US, particularly Venezuela. Venezuela responds U.S military presence by using offensive military strategy. This research is a qualitative case study design. The results suggest that in the security dilemma situation, Venezuela can take a defensive strategy to allow cooperation with other countries in order to avoid the war.